A Call to Arms: Propaganda, Public Opinion, and Newspapers in the Great War - Paddock, Troy R. E. (Praeger Publishers, 2004)
World War I highlighted the influence of newspapers in rousing and maintaining public support for the war effort. Discussions of the role of the press in the Great War have, to date, largely focused on atrocity stories. This book offers the first comparative analysis of how newspapers in Great Britain, France, Russia, Germany, and Austria-Hungary attempted to define war, its objectives, and the enemy. Presented country-by-country, expert essays examine, through use of translated articles from the contemporary press, how newspapers of different nations defined the war for their readership and t., World War I highlighted the influence of newspapers in rousing and maintaining public support for the war effort. Discussions of the role of the press in the Great War have, to date, largely focused on atrocity stories. This book offers the first comparative analysis of how newspapers in Great Britain, France, Russia, Germany, and Austria-Hungary attempted to define war, its objectives, and the enemy. Presented country-by-country, expert essays examine, through use of translated articles from the contemporary press, how newspapers of different nations defined the war for their readership and t
Keywords: Press coverage; Propaganda; World War; 1914-1918; Public opinion; Press and propaganda; War; World War; 1914-1918; dept.his; faculty_collection